PENGEMBANGAN KOMPONEN INSTRUMEN TERPADU (KIT) PRAKTIKUM KIMIA - Tiara Juliani; Elvinawati; Febrian Solikhin (ALOTROP, 2024)
This research to determine the feasibility of the practicum KIT, responses and students' psychomotor abilities after using the developed KIT alternative media.  The development of this chemistry practicum KIT uses ADDIE development.  This research was conducted at SMA Negeri 9 Kota Bengkulu with research subjects namely 12 students of class XI MIPA 2 for small group trials and all students of class XI MIPA 3 SMA Negeri 8 Kota Bengkulu and SMA Negeri 9 Kota Bengkulu for large group trials.  The instruments in this research are interview sheets, student needs questionnaires, validation sheets, student response questionnaires, and psychomotor assessment sheets.  The results of this research obtained (1) The feasibility level of the chemistry practicum KIT was 94,05% with a very valid category, (2) The results of students' responses to the practicum KIT on calorimeter material obtained a percentage of 89,06% in the very good category, (3) The participants' psychomotor abilities  students obtained an average percentage at SMA Negeri 8 Kota Bengkulu of 92,17% and SMA Negeri 9 Kota Bengkulu of 96,95% the very good category.  The results of this research show that a chemistry practical KIT on calorimeter material has been developed which is very suitable for use and application in the learning process